Vibration analysis of shearer cutting system using mechanical hydraulic collaboration simulation. (December 2017) - Zeng, Qingliang; Gao, Kuidong; Zhang, Haizhong; Jiang, Shoubo; Jiang, Kao
The cutting unit of a mining shearer is composed of a drum, gear transmission and hydraulic height adjusting mechanism. To obtain the dynamic characteristics of crucial components in the coal cutting process, a model of a drum cutting coal was constructed using LS-DYNA. The model of gear transmission was constructed with Adams, and a model of the hydraulic height adjusting system was constructed with AMESim. Data transmission and co-simulation of these three models were implemented with MATLAB. Changes of the meshing force, acceleration and amplitude–frequency characteristics of key gears under different conditions were obtained. From the research, we conclude that it is effective and feasible to apply the multi-software co-simulation used by this paper to research a complex mechanical–hydraulic system such as a shearer cutting unit; supports from a hydraulic cylinder can decrease the meshing force of gears to some extent; and the meshing force of gears increases significantly as the mining height of the drum increases.